“Glory to God in the highest, and on earth peace”: church singing in occupied Pskov (1941–1944) - I. V. Gerasimova (Вестник Свято-Филаретовского института, 2022)
The article reconstructs the organization of church singing in occupied Pskov in 1941–1944, associated with the restoration of worship in churches closed in the pre-war period, headed by the Holy Trinity Cathedral — a former anti-religious museum. Documentary and narrative sources were involved in the work, including published memoirs of members of the Pskov Orthodox Mission, the manuscript of the priest Vasily Lirin “Church Chronicle” of the Church of the Vladimir Icon of the Mother of God of the village of Lisye, Pechersk district (1927–1945), oral testimonies of Pskov residents, the occupation press — the newspaper “Za Rodinu” (Dno, Pskov), the magazine “Orthodox Christian” and other publications of the time being studied, as well as notes of church works. Revival of church life in Pskov and the opening of churches led to the creation of church choirs, ensembles and the activation of not only liturgical, but also concert activities. The structure of the choir of the Varlaam church is reconstructed according to the memoirs of L. I. Manukhina and the administration of worship by Bezpopovtsy according to the stories of L. K. Rozhkova. The central figure of this movement was the priest, composer and regent M. F. Grivsky, who came from Riga to Pskov, under whose leadership the united choir of Pskov church singers operated. The consolidated choir took part in festive divine services and important events, spiritual concerts and radio broadcasts. The available sources contain a repertoire of works performed at concerts, consisting of works by prerevolutionary figures of church music. The article puts in the historical context and analyzes the Small Doxology of Grivsky found among the notes of the library of the Pskov-Pechory Monastery with the date of publication, and probably the creation of 1943. This work is published in the appendix to the article.